The Howieson's Poort fauna from Sibudu Cave: Documenting continuity and change within Middle Stone Age industries. Issue 107 (June 2017) - Clark, Jamie L.
Abstract: The Howieson's Poort (HP; ∼65–59 ka) continues to be a source of interest to scholars studying human behavioral evolution during the Late Pleistocene. This is in large part because the HP preserves evidence for a suite of innovative technologies and behaviors (including geometric backed tools and engraved ostrich eggshell), but also because the disappearance of the innovative behaviors associated with this phase is not well understood. Here, I present taphonomic and taxonomic data on the full sample of macromammal remains excavated from the HP deposits at Sibudu Cave under the direction of Lyn Wadley. With a total number of identified specimens (NISP) of 5921, Sibudu provides the largest sample of HP fauna published to date. Taken as a whole, the data suggest a focus on a diverse range of prey. Ungulates dominate the assemblage, as do taxa that preferentially inhabit closed (particularly forested) environments. Small bovids are common throughout; blue duiker (Philantomba monticola ) alone comprises ∼33% of the total NISP. A diverse smaller game assemblage is also present. Taphonomic data implicate humans as the primary contributor to the fauna; however, low levels of gastric etching (∼1% of the NISP) suggest that non-human agents may have played some role in the accumulation of the smaller game. Despite broad similarities in the fauna, a number of directional trends are evidenced. Most notably, the lowermost deposits of the HP contain the highest frequency of blue duiker and other small ungulates, taxa which prefer closed environments, and miscellaneous smaller game. All of these decline throughout the HP, and these differences are statistically significant. After considering possible explanations for these trends, I discuss the potential implications of the variation evidenced in the assemblage to our understanding of the onset—and disappearance—of this important substage of the MSA.